PENEGAKAN HUKUM LINGKUNGAN DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN - UTOMO, DARMAWAN TRI BUDI; DEWI, MIEKE ANGGRAENI; KUSWARINI, KUSWARINI (GANEC SWARA, 2023)
This article delves into the crucial significance of protecting the environment against damage and the legal enforcement concepts, both civil and criminal, against environmental offenders. The research employs a juridical-normative approach, utilizing legislative regulations. The findings of the study indicate that the importance of safeguarding the environment against damage is manifested in endeavors to realize human health, economic aspects, global climate stability, and global responsibility. In sustainable development, environmental protection is considered a foundation for achieving these goals. Awareness of the close relationship between law and sustainable development is pivotal for success. The concept of legal enforcement comprises two main perspectives: civil law and criminal law. Civil law emphasizes the responsibility for compensation and absolute liability, while criminal law involves processes of investigation, prosecution, and the implementation of judicial decisions. Criminal sanctions can be applied at the individual or corporate level, emphasizing deterrence effects and corporate responsibility. In conclusion, to enhance environmental law enforcement, the government needs to intensify surveillance and the application of criminal sanctions. Effective coordination among relevant institutions, such as sectoral authorities, in permitting and environmental monitoring is crucial. Active community involvement in reporting environmental violations and supporting conservation policies is highly essential.